1979
DOI: 10.1126/science.451556
|View full text |Cite
|
Sign up to set email alerts
|

GABA Receptor Control of Parasympathetic Outflow to Heart: Characterization and Brainstem Localization

Abstract: Blockade of gamma-aminobutyric acid (GABA) receptor function by direct microinjection of the GABA receptor antagonist bicuculline into the nucleus ambiguus of the brainstem produced a marked, dose-related depression of heart rate and blood pressure which was mediated by the vagus nerve. This effect was not obtained in other regions of the brainstem and was reversed by the GABA receptor agonist muscimol. These data indicate that the nucleus ambiguus may be the site of a GABA receptor-mediated inhibition of vaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(46 citation statements)
references
References 16 publications
3
42
1
Order By: Relevance
“…For example, injection of a GABA receptor antagonist into the nucleus ambiguous of the brainstem shows a dose-dependent decrease in heart rate and blood pressure. This effect does not occur in any other areas of the brainstem, suggesting that GABA inhibits vagal outflow from the nucleus ambiguous (DiMicco et al 1979). Inspiratory-modulated GABAergic neurons may be responsible for the inhibition of parasympathetic cardioinhibitory neurons that result in respiratory sinus arrhythmia (Frank and Mendelowitz 2012).…”
Section: Possible Role Of Membrane Potential In Cardiorespiratory Modmentioning
confidence: 90%
“…For example, injection of a GABA receptor antagonist into the nucleus ambiguous of the brainstem shows a dose-dependent decrease in heart rate and blood pressure. This effect does not occur in any other areas of the brainstem, suggesting that GABA inhibits vagal outflow from the nucleus ambiguous (DiMicco et al 1979). Inspiratory-modulated GABAergic neurons may be responsible for the inhibition of parasympathetic cardioinhibitory neurons that result in respiratory sinus arrhythmia (Frank and Mendelowitz 2012).…”
Section: Possible Role Of Membrane Potential In Cardiorespiratory Modmentioning
confidence: 90%
“…In vivo studies show that microinjection of bicuculline into the nucleus ambiguus of the brainstem produces a decrease in the heart rate and blood pressure that is mediated by the vagus nerve (DiMicco et al, 1979). This indicates that the nucleus ambiguus is a site of GABA receptormediated inhibition of vagal outflow to the heart (DiMicco et al, 1979;Williford et al, 1980). In vitro studies reflect this by demonstrating that cardiac vagal neurons in the nucleus ambiguus are constantly inhibited by spontaneous GABAergic synaptic input; one likely GABAergic pathway may arise from the NTS (Wang et al, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Most parasympathetic activity regulating heart rate and cardiac function originates from central parasympathetic cardiac neurons within the nucleus ambiguus (Mendelowitz, 1999;Wang et al, 2001a,b). Recent studies have re-vealed two major synaptic inputs to cardiac vagal neurons from the NTS: an excitatory glutamatergic pathway (Mendelowitz, 1998;Neff et al, 1998b) and an inhibitory GABAergic input (DiMicco et al, 1979;Wang et al, 2001a,b). Nicotine has also been found to facilitate glutamatergic transmission, as well as to directly activate vagal cardioinhibitory neurons (Neff et al, 1998a (Sim and Childers, 1997), in situ hybridization, and immunohistochemistry (Neal et al, 1999a,b;Houtani et al, 2000;Mollereau and Mouledous, 2000) have identified both ORL 1 receptors (Sim and Childers, 1997;Neal et al, 1999a;Houtani et al, 2000;Mollereau and Mouledous, 2000) and nociceptin itself (Neal et al, 1999b) within the NTS and nucleus ambiguus.…”
mentioning
confidence: 99%
“…Premotor cardiac vagal neurons are located in the nucleus ambiguus and the dorsal motor nucleus of the vagus (DiMicco et al 1979;Mendelowitz 1999Mendelowitz , 1996Standish et al 1995;Stuesse 1982). Since premotor cardiac vagal neurons are intrinsically silent, their activity is determined by excitatory and inhibitory synaptic inputs (Mendelowitz 1999(Mendelowitz , 1996Mendelowitz and Kunze 1991).…”
Section: Introductionmentioning
confidence: 99%